Soberania e segurança alimentar em assentamentos rurais: o caso dos assentamentos PDS Mário Lago e Santa Helena no estado de São Paulo - Veron, Ana Claudia Olartechea (2025)
The agribusiness sector, as the hegemonic agri-food system, has not been effective in combating hunger due to its dynamics, which strengthen the development of large transnational groups that control the production and commercialization of agricultural products, prioritizing the production of commodities over food. In this context, agroecology emerges as an alternative agri-food system where farmers and consumers take center stage, representing a necessary condition for transforming the current structure of the agri-food system. This transformation aims to reshape the way food is produced, distributed, and commercialized. Given this, this study aims to investigate the potentialities and challenges in ensuring food security and sovereignty in two rural settlements classified as Sustainable Development Projects (PDS): PDS Santa Helena and PDS Mário Lago, located in the municipalities of São Carlos (SP) and Ribeirão Preto (SP), respectively. These settlements implement a strategic agroecological project to improve the food and nutritional security of settled families while developing a production model distinct from the dominant sugar-alcohol agribusiness in the region. Methodologically, the investigation was structured through field research with semi-structured interviews and the application of the Brazilian Food Insecurity Scale questionnaire in both PDS Santa Helena and PDS Mário Lago settlements in São Paulo. The study concludes that, unlike the national reality, the PDS model settlements, through collective and cooperative work and agroecological production, contribute to reducing food and nutritional insecurity among settled peasant families.